2017
DOI: 10.1002/hbm.23808
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of motion perceptual learning in noise

Abstract: Practice improves our perceptual ability. However, the neural mechanisms underlying this experience-dependent plasticity in adult brain remain unclear. Here, we studied the long-term neural correlates of motion perceptual learning. Subjects' behavioral performance and BOLD signals were tracked before, immediately after, and 2 weeks after practicing a motion direction discrimination task in noise over six daily sessions. Parallel to the specificity and persistency of the behavioral learning effect, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…After concluding that the groups do not differ on any of the GABA+ or Glx measures, we turned to examine whether neurometabolite levels are associated with sensory sensitivity or with ASD symptomatology, and whether these associations differ in direction or magnitude between the groups, as previously suggested [Brix et al, 2015;Robertson et al, 2016]. We estimated visual sensitivity by measuring thresholds for contrast detection, a task thought to rely on early visual cortex computations [Boynton, Demb, Glover, & Heeger, 1999;Ress & Heeger, 2003], and thresholds for motion discrimination, a task associated with MT+ activation [Chen, Lu, Shao, Weng, & Fang, 2017;Turkozer, Pamir, & Boyaci, 2016]. We correlated these thresholds with GABA+ and Glx measurements in the corresponding ROIs in the visual cortex (left and right MT+ for motion and occipital for contrast), however no significant correlations were observed (|r 21-38 | < 0.29, uncorrected P > 0.217).…”
Section: Resultsmentioning
confidence: 99%
“…After concluding that the groups do not differ on any of the GABA+ or Glx measures, we turned to examine whether neurometabolite levels are associated with sensory sensitivity or with ASD symptomatology, and whether these associations differ in direction or magnitude between the groups, as previously suggested [Brix et al, 2015;Robertson et al, 2016]. We estimated visual sensitivity by measuring thresholds for contrast detection, a task thought to rely on early visual cortex computations [Boynton, Demb, Glover, & Heeger, 1999;Ress & Heeger, 2003], and thresholds for motion discrimination, a task associated with MT+ activation [Chen, Lu, Shao, Weng, & Fang, 2017;Turkozer, Pamir, & Boyaci, 2016]. We correlated these thresholds with GABA+ and Glx measurements in the corresponding ROIs in the visual cortex (left and right MT+ for motion and occipital for contrast), however no significant correlations were observed (|r 21-38 | < 0.29, uncorrected P > 0.217).…”
Section: Resultsmentioning
confidence: 99%
“…They also reported modest individual variability in the coherence-response function, but not whether such variability corresponds to differences in perception. A more recent study has found a correspondence between improved behavioral performance and fMRI response changes in MT following perceptual learning (Chen et al, 2017). Specifically, subjects with smaller thresholds in a motion discrimination paradigm following extensive training also showed greater sharpening of tuning within MT, as assessed by multi-voxel pattern analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Here, we again chose to focus on neural processing within cortical area MT, in order to test our above hypothesis regarding a link between Glx, neural responses, and task performance. Neural responses within MT in both monkeys (Britten et al, 1992; Churan et al, 2008; Huk and Shadlen, 2005; Liu et al, 2016) and humans (Chen et al, 2017; Huk et al, 2001; Rees et al, 2000; Schallmo et al, 2018; Tadin et al, 2011; Turkozer et al, 2016) are known to be tightly linked to motion perception. In particular, studies in humans suggest that motion duration thresholds (Tadin, 2015; Tadin et al, 2003) – the amount of time that a stimulus needs to be presented to accurately discriminate motion direction – are shorter under conditions that elicit higher MT responses (Schallmo et al, 2018; Tadin et al, 2011; Turkozer et al, 2016), in agreement with our recent computational work (Schallmo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Mollon and Danilova (1996) hypothesized that learning occurs at a more central site but still predicts orientation and location specificity of learning. Models like improved readout or reweighting of representation neurons (e.g., V1) ( Poggio et al, 1992 ; Dorsher and Lu, 1998 ) and the involvement of high-level processes beyond the visual cortex ( Li W. et al, 2008 ) have been proposed in the last decades and received support from psychophysical ( Liu, 1999 ; Liu and Weinshall, 2000 ; Xiao et al, 2008 ; Zhang et al, 2010 ), neurophysiological ( Law and Gold, 2008 ), and brain imaging studies ( Chen et al, 2015 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%